THE RIGHT TO ENVIRONMENTAL INFORMATION IN INTERNATIONAL LEGAL DOCUMENTS - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The paper deals with the issue of regulation of the right of natural and legal persons to environmental information, in relevant international legal documents. There is a survey of certain international conventions which envisage this right in their field of regulation. The right to access the information is in details regulated in the Aarhus Convention, which comprises significant part of this paper. This kind of regulation of the right to environmental information has performed a significant influence on states and international organizations, which created their domestic and international rules, using the solutions from this Convention. The European Union has enacted a significant number of directives on the right of a public to receive environmental information. The special emphasis will be on the work of the Aarhus Convention’s Compliance Committee which has a significant role in supervising and deciding about the compliance with the application of the Convention in its member states.